Fabric variability within layered Fe-oxide deposits in Mid-late Miocene sedimentary formations, NW Borneo: impact on facies architectural interpretations - Padmanabhan, Eswaran; Kessler, F. (Geological Society of Malaysia, 2008)
Iron (Fe) can accumulate in various forms in sedimentary environments that experience alternating moisture conditions, hydration and dehydration processes and redox processes. It has been pointed out that there is a major gap in the understanding of the composition of mixed solid-phase minerals, their size, morphology and arrangement in the matrix and possible interactions with pore solutions and the environment of deposition. Variations in the fabric within concretions in some Mid-Late Miocene beds in NW Borneo suggest that there were more changes in the energy levels and processes involved than what has been perceived from routine fabric analyses of the sedimentary rocks. The sedimentary rocks are essentially carbonaceous claystones containing varying amounts of highly restricted marginal-marine fauna. The fauna probably accumulated in brackish waters, and comprise in-situ buried turritellid snails, fish teeth and bone tissue, fragments of crabs, very few forams and possibly ostracod shells. Evidence exists to support the concept of reworked cobble or pebble-sized fossiliferous mudstones picking up contemporaneous shell fragments in these restricted conditions. Iron oxide content is seen as (i) micrite-size primary components forming part of a muddy matrix and (ii) diagenetic coatings. Coatings occur in a non-rhythmical pattern after the formation of mudstones, and the reworking of the material and subsequent coatings by iron. Iron coated pebbles/cobbles may experience re-cementing into large sheets giving the appearance of red beds. These occur under some very special redox conditions. These iron-concretion rich horizons appear then to represent extreme (climatic, etc) facies developments that were restricted to coastal areas during Mid-Late Miocene. Present-day iron deposition processes might be a key to understanding past processes. This study forms the basis for an enhanced understanding on facies architectural interpretations.